Mentalizing countertransference? A model for research on the elaboration of countertransference experience in psychotherapy - Barreto, João Francisco (2019)
As a construct, the elaboration of countertransference experience (ECE) is intended to depict the implicit and explicit psychological work to which therapists submit their experiences with clients. Through ECE, defined as a mentalizing process of a particular kind, therapists' experiences are presumed to acquire and increase in mental quality and become available for meaning-making and judicious clinical use. In this paper, we claim that such an ongoing process facilitates engagement with common therapeutic factors, such as the therapeutic alliance and countertransference management, enhancing therapist responsiveness in psychotherapy. We synthesize relevant literature on countertransference, mentalization, and, in particular, therapists' mentalization, informed by a systematic literature review. As a result, we propose a model for assessing ECE in psychotherapy, comprising 6 diversely mentalized countertransference positions (factual-concrete, abstract-rational, projective-impulsive, argumentative, contemplative-mindful, and mentalizing), 2 underlying primary dimensions (experiencing, reflective elaboration), and 5 complementary dimensions of elaboration. Strengths and limitations of the model are discussed.